2009
DOI: 10.1063/1.3080173
|View full text |Cite
|
Sign up to set email alerts
|

Study of monoclinic-tetragonal-cubic phase transition in Pb(Zn1/3Nb2/3)O3–0.08PbTiO3 single crystals by micro-Raman spectroscopy

Abstract: The relaxor ferroelectric Pb(Zn1/3Nb2/3)O3–0.08PbTiO3 (PZN–0.08PT) single crystal has been investigated using polarized micro-Raman scattering technique in a wide temperature range from −150 to 350 °C. Raman spectra of the crystal at temperatures lower than 90 °C show 11 modes over a frequency range of 100–1000 cm−1. There are 12 Raman active vibration modes in the monoclinic structure of relaxor ferroelectrics according to the group theory analysis. Thus the structure of PZN-0.08PT single crystal at low tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 36 publications
5
19
0
Order By: Relevance
“…One can see that the σ, R and <Ti-O> modes reveal a blue shift as well as a decrement of the peak intensity with increasing temperatures. These results are consistent well with the observations reported by Mishra et al [19] and Cheng et al [20]. The gradual shift of these modes also implies that the structure evolution of PZN-9PT is continuous rather than mutational, in agreement with the XRD results.…”
Section: Structure Phase Transition Of Pzn-9pt Crystalssupporting
confidence: 83%
“…One can see that the σ, R and <Ti-O> modes reveal a blue shift as well as a decrement of the peak intensity with increasing temperatures. These results are consistent well with the observations reported by Mishra et al [19] and Cheng et al [20]. The gradual shift of these modes also implies that the structure evolution of PZN-9PT is continuous rather than mutational, in agreement with the XRD results.…”
Section: Structure Phase Transition Of Pzn-9pt Crystalssupporting
confidence: 83%
“…One can see that the σ, R, and <Ti-O> modes reveal a blue shift as well as a decrement of the peak intensity with increasing temperatures. These results are well consistent with the observations reported by Mishra et al [19] and Cheng et al [20]. The gradual shift of these modes also implies that the structure evolution of PZN-9PT is continuous rather than mutational, in agreement with the XRD results.…”
Section: Structure Phase Transition Of Pzn-9pt Crystalssupporting
confidence: 83%
“…Sample temperatures ranging from 298 to 343 K were controlled using a Linkam TS600 hot stage with a temperature stability of ±0.5 K. The previous study 17 using this spectrometer showed that 5 min is long enough to achieve the thermalization of the system; therefore, in this study, the temperature was held fixed for at least 5 min at each selected temperature (298 and 343 K) in order to obtain the thermalization of the system. The Raman spectra were measured in both crossed Z(XY)Z̅ (VH) and parallel Z(XY) Z̅ (VV) polarizations, where X, Y, and Z are the cubic axes.…”
Section: Methodsmentioning
confidence: 99%